Construction law handbook incorporating the Construction law handbook newsletters issues 42 to 47 (November 2007 to September 2008) - Ramsey, Vivian (Thomas Telford, 2009)
The standard on construction law, providing up-to-date, clear and easily accessible information in a single volume. Experts from the largest specialist construction law firms and leaders from within the construction industry have combined their knowledge to produce this authoritative resource.